Nutrition and physical activity in the prevention and treatment of sarcopenia: systematic review - Beaudart, C.; Dawson, A.; Shaw, S. C.; Harvey, N. C.; Kanis, J. A.; Binkley, N.; Reginster, J. Y.; Chapurlat, R.; Chan, D. C.; Bruyère, O.; Rizzoli, R.; Cooper, C.; et al. (Osteoporosis international, 2017)
Summary This systematic review summarizes the effect of combined exercise and nutrition intervention on muscle mass and muscle function. A total of 37 RCTs were identified. Results indicate that physical exercise has a positive impact on muscle mass and muscle function in subjects aged 65 years and older. However, any interactive effect of dietary supplementation appears to be limited. Introduction In 2013, Denison et al. conducted a systematic review including 17 randomized controlled trials (RCTs) to explore the effect of combined exercise and nutrition intervention to improve muscle mass, muscle strength, or physical performance in older people. They concluded that further studies were needed to provide evidence upon which public health and clinical recommendations could be based. The purpose of the present work was to update the prior systematic review and include studies published up to October 2015. Methods Using the electronic databases MEDLINE and EMBASE, we identified RCTs which assessed the combined effect of exercise training and nutritional supplementation on muscle strength, muscle mass, or physical performance in subjects aged 60 years and over. Study selection and data extraction were performed by two independent reviewers. Results The search strategy identified 21 additional RCTs giving a total of 37 RCTs. Studies were heterogeneous in terms of protocols for physical exercise and dietary supplementation (proteins, essential amino acids, creatine, β-hydroxy-β-methylbuthyrate, vitamin D, multi-nutrients, or other). In 79% of the studies (27/34 RCTs), muscle mass increased with exercise but an additional effect of nutrition was only found in 8 RCTs (23.5%). Muscle strength increased in 82.8% of the studies (29/35 RCTs) following exercise intervention, and dietary supplementation showed additional benefits in only a small number of studies (8/35 RCTS, 22.8%). Finally, the majority of studies showed an increase of physical performance following exercise intervention (26/28 RCTs, 92.8%) but interaction with nutrition supplementation was only found in 14.3% of these studies (4/28 RCTs). Conclusion Physical exercise has a positive impact on muscle mass and muscle function in healthy subjects aged 60 years and older. The biggest effect of exercise intervention, of any type, has been seen on physical performance (gait speed, chair rising test, balance, SPPB test, etc.). We observed huge variations in regard to the dietary supplementation protocols. Based on the included studies, mainly performed on well-nourished subjects, the interactive effect of dietary supplementation on muscle function appears limited.